Complete denture with pharyngeal bulb prosthesis. (18th April 2013) - Naveen, YG; Jagadeesh, MS; Prajapati, Paranjay; Mallikarjuna, Rachappa
Abstract : Velopharyngeal dysfunction is the inability of the soft palate to affect complete seal with the posterior or lateral pharyngeal walls. Rehabilitation of these patients with palatal defects is challenging for both surgical and prosthetic fields of dentistry. The development of sophisticated surgical techniques and procedures has greatly enhanced the rehabilitation of congenital or acquired palatal defects. However, some of these patients may present oral or systemic factors contraindicating surgical intervention. In addition, since total elimination of these defects surgically has not yet become a reality, there exists a patient population for whom non-surgical rehabilitation must be approached with the help of prosthesis and such prosthesis must restore the basic functions of mastication, deglutition and speech production. Here a non-surgical approach of rehabilitation of such defect is presented in the form of a case report of pharyngeal bulb prosthesis given for a patient with a soft palate defect.